Yellow brick war - Paige, Danielle (Novelist) (Paige, Danielle (Novelist). Dorothy must die series., 2016)
To fight for Oz and save Kansas from power-hungry dictator Dorothy's latest plot, Amy teams up with the Revolutionary Order of the Wicked and finds herself working alongside the Wicked Witch of the West.